Simultaneous activation of the liver X receptors (LXRα and LXRβ) drives murine collagen-induced arthritis disease pathology. Issue 12 (22nd August 2011) - Asquith, Darren L; Miller, Ashley M; Reilly, James; Kerr, Shauna; Welsh, Paul; Sattar, Naveed; McInnes, Iain B
Abstract : Background: It has previously been shown that dual activation of the Liver X Receptors (LXRα and LXRβ) by the agonist, GW3965, enhances pathology in a murine model of collagen-induced arthritis. Objective: To determine whether LXRα or LXRβ have discrete roles in driving articular inflammation. Methods: Arthritis was induced in male C57BL/6 wild-type (WT), LXRα−/−, LXRβ−/− and LXRα/β double KO mice by injection with type II collagen and treated with 30 mg/kg of the LXR agonist GW3965 or vehicle control. The mice were monitored for articular inflammation and cartilage degradation by scoring for clinical signs of arthritis and by histological examination of the joints. Results: Administration of 30 mg/kg GW3965 significantly increases the severity of arthritis in WT but not LXRα−/−, LXRβ−/− or LXRα/β KO mice as assessed by an increase in the clinical score, paw thickness and articular histological analysis. Conclusion: The proinflammatory effects associated with the administration of GW3965 are mediated specifically through LXRs. The absence of increased disease severity in the LXRα−/− and LXRβ−/− GW3965-treated groups shows for the first time that agonism of both LXRα and LXRβ is required to drive proinflammatory pathways in vivo.